Pythium insidiosum: inhibitory effects of propolis and geopropolis on hyphal growth - Araújo, Maria José Abigail Mendes [UNESP]; Bosco, Sandra de Moraes Gimenes [UNESP]; Sforcin, José Maurício [UNESP] (Springer Nature, 2016)
Propolis and geopropolis are resinous products of bees showing antimicrobial effects. There is no data concerning their action against Pythium insidiosum – the causative agent of pythiosis, a pyogranulomatous disease of the subcutaneous tissue that affects mostly horses, dogs and humans. Fragments of 15 isolates of P. insidiodum were incubated with propolis and geopropolis extracts and evaluated for up to seven days to detect the minimal fungicidal concentration (MFC). Propolis inhibited three isolates at 1.0 mg mL−1 after 24 h and all other isolates at 3.4 mg mL−1. Geopropolis led to more variable results, exerting predominantly a fungistatic action than a fungicidal one. Propolis was more efficient than geopropolis in inhibiting P. insidiosum since lower concentrations led to no growth after 24 h. This effect may be due to propolis chemical composition, which has more active compounds than geopropolis. Propolis seemed to be a good candidate for in vivo studies, since treatment with conventional antifungal compounds is difficult in most of the cases, requiring extensive surgical debridement.
Keywords: Africanized honeybees; Geopropolis; Propolis; Pythium insidiosum; Stingless bees